Characteristics of healthy school-age children's visual evoke potentials - Shu-Yao Ning (Guoji Yanke Zazhi, 2017)
AIM: To conclude the characteristics of flash visual evoke potentials(FVEP), and pattern visual evoke potentials(PVEP)of the healthy school-age children. And to compare the two methods, in order to find the association of them, and to find the impact of sex, age, and the other biological variables. METHODS: A total of 101 healthy children were recruited(age from 5 to 14.4y, mean 8.27y). Each of them was underwent FVEP and PVEP examinations. Then the results were statistically analyzed by SPSS 13.0. RESULTS: The curves of PVEP are simple and stable, while FVEP waveforms are variable. The latency of P100 of females is shorter than males. However there was no significant difference for FVEP in sex control. To compare the parameters between the two hemispheres, the amplitude of P100 of left eyes were higher than the right side. FVEP showed no difference in the two hemispheres either. There was no significant difference for age-dependent decreased in neither PVEP nor FVEP. And in a regression analysis of the FVEP and PVEP, we could not find the inner connection of the two methods. CONCLUSION: Based on our research, there were no significant differences in age level or sex control in the period of school-age children. And there is no inner connection of the two methods. The differences between the PVEP and FVEP results might be due to the origin of these two responses. And these two stimuli should be used in a complementary manner not as alternative examinations.